Dampak Ekonomi Makro terhadap Inward Forect Direct Investment (FDI) di Indonesia - Almustofa, Muhammad Ubaidillah; Mawardi, Imron; Widiastuti, Tika; Sukmana, Raditya; Febrianti, Puput Rosita; Hanoraga, Tony; Nisa, Khairun (Institut Teknologi Sepuluh Nopember, 2024)
This paper investigates the country-specific risks associated with inward foreign direct investment (FDI) in Indonesia and analyzes the broader macroeconomic consequences. The study utilizes the Autoregressive Distributed Lag (ARDL) model to examine both the short-term and long-term cointegration between macroeconomic factors and foreign investment inflows. The research is based on secondary annual time series data from 1984 to 2015. In the short term, the exchange rate has a crucial impact, as depreciation of the Indonesian Rupiah leads to a higher inflow of FDI. However, while financial variables do not significantly affect the dependent variable in the long term, independent variables such as inflation, GDP growth risk, and economic and political risks do have a considerable effect. Rational foreign investors prioritize maximizing returns on their investments by closely monitoring the volatility of macroeconomic conditions. Thus, it is imperative for the government to regulate these aspects to enhance the inflow of foreign investments.